MATHEMATICAL MODEL DEVELOPMENT OF HEAT AND MASS EXCHANGE PROCESSES IN THE OUTDOOR SWIMMING POOL - Shaptala, M. V.; Shaptala, D. E. (Science and Transport Progress, 2014)
Purpose. Currently exploitation of outdoor swimming pools is often not cost-effective and, despite of their relevance, such pools are closed in large quantities. At this time there is no the whole mathematical model which would allow assessing qualitatively the effect of energy-saving measures. The aim of this work is to develop a mathematical model of heat and mass exchange processes for calculating basic heat and mass losses that occur during its exploitation. Methodology. The method for determination of heat and mass loses based on the theory of similarity criteria equations is used. Findings. The main types of heat and mass losses of outdoor pool were analyzed. The most significant types were allocated and mathematically described. Namely: by evaporation of water from the surface of the pool, by natural and forced convection, by radiation to the environment, heat consumption for water heating. Originality. The mathematical model of heat and mass exchange process of the outdoor swimming pool was developed, which allows calculating the basic heat and mass loses that occur during its exploitation. Practical value. The method of determining heat and mass loses of outdoor swimming pool as a software system was developed and implemented. It is based on the mathematical model proposed by the authors. This method can be used for the conceptual design of energy-efficient structures of outdoor pools, to assess their use of energy-intensive and selecting the optimum energy-saving measures. A further step in research in this area is the experimental validation of the method of calculation of heat losses in outdoor swimming pools with its use as an example the pool of Dnipropetrovsk National University of Railway Transport named after Academician V. Lazaryan. The outdoor pool, with water heating-up from the boiler room of the university, is operated year-round.